2012
DOI: 10.1103/physrevb.86.064510
|View full text |Cite
|
Sign up to set email alerts
|

Geometry-related magnetic interference patterns in longSNSJosephson junctions

Abstract: We have measured the critical current dependence on the magnetic flux of two long SNS junctions differing by the normal wire geometry. The samples are made by a Au wire connected to W contacts, via focused ion beam assisted deposition. We could tune the magnetic pattern from the monotonic Gaussian-like decay of a quasi-one-dimensional (1D) normal wire to the Fraunhofer-like pattern of a square normal wire. We explain the monotonic limit with a semiclassical 1D model, and we fit both field dependencies with num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 15 publications
4
40
0
Order By: Relevance
“…The measured SQI pattern at V BG = −0.3 V is well reproduced by the theoritical curves for a (quasi) 1D JJ [ Fig. 3(c)], as described [27,36] and observed before [36,37]. Entering the 1D regime is in line with having a single edge with (110) facet and enhanced edge conduction in JJ2 [ Fig.…”
supporting
confidence: 70%
“…The measured SQI pattern at V BG = −0.3 V is well reproduced by the theoritical curves for a (quasi) 1D JJ [ Fig. 3(c)], as described [27,36] and observed before [36,37]. Entering the 1D regime is in line with having a single edge with (110) facet and enhanced edge conduction in JJ2 [ Fig.…”
supporting
confidence: 70%
“…The vortices could be detected directly by a scanning tunneling probe [31][32][33], or indirectly through the fluxdependent Fraunhofer oscillations [34,35]-we have found that the transition from a 1D to a 2D arrangement of vortices is accompanied by a slow-down of the decay of the oscillation amplitude from 1/ to 1/ √ . A particularly intriguing feature of the current vortex lattice is the reconstruction at the edge, resulting in an edge channel of width l m parametrically larger than the lattice constant.…”
Section: Discussionmentioning
confidence: 93%
“…For junction widths comparable to the S-section coherence length, i.e. the narrow junction limit, this becomes a quasi-Gaussian, monotonic decay of the critical current 7,10,11 . Recently, attention has been given to nanoscale, quasi one-dimensional (1D) SN S junctions, such as those readily engineered by contacting semiconductor nanowires with superconducting leads [12][13][14][15][16] .…”
mentioning
confidence: 99%
“…Planar SN S junctions of width large compared to the S-section superconducting coherence length have been studied in great detail 6 (width refers to the dimension perpendicular to the current). These have revealed, for example, Fraunhofer oscillations of the critical current I c with respect to an externally applied out-of-plane magnetic field [7][8][9] . For junction widths comparable to the S-section coherence length, i.e.…”
mentioning
confidence: 99%